2017
DOI: 10.2217/fon-2017-0405
|View full text |Cite
|
Sign up to set email alerts
|

Can radiotherapy potentiate the effectiveness of immune checkpoint inhibitors in lung cancer?

Abstract: Systemic therapy including platinum-based chemotherapy and targeted therapy has been a mainstay of treatment for the majority of patients with metastatic non-small-cell lung cancer (NSCLC). Recent breakthroughs in immune checkpoint blockade, along with a deeper understanding of tumor immune biology, have led to a paradigm shift in the standard of care for cancer treatment. By activating the immune system to recognize and eliminate cancer, immune checkpoint blockade has the potential to elicit durable responses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 31 publications
(49 reference statements)
0
7
0
Order By: Relevance
“…Several recent reviews have discussed the potential of combining immunotherapy and radiotherapy, including for lung cancer, with respect to clinical efficacy [37,38,39,40,41,42,43,44,45]. The recent review from Ko et al published in June 2018 nicely summarizes planned and ongoing trials of combined radioimmunotherapy in patients with NSCLC with respect to present knowledge [37].…”
Section: Combining Radiotherapy and Immunotherapy In Lung Cancermentioning
confidence: 99%
“…Several recent reviews have discussed the potential of combining immunotherapy and radiotherapy, including for lung cancer, with respect to clinical efficacy [37,38,39,40,41,42,43,44,45]. The recent review from Ko et al published in June 2018 nicely summarizes planned and ongoing trials of combined radioimmunotherapy in patients with NSCLC with respect to present knowledge [37].…”
Section: Combining Radiotherapy and Immunotherapy In Lung Cancermentioning
confidence: 99%
“…5−11 However, less than 20% of patients benefit from immunotherapy. 12 The benefit of immunotherapy can be extended to a broader population of cancer patients by using adjuvant chemo-or targeted therapies, which can induce an immunogenic cell death, liberate neoantigens, and therefore further enhance the antitumor immune responses. 13 Alternatively, the efficacy of immunotherapy can be maximized by preselection of patients who are candidates for immunotherapy.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In a phase I KEYNOTE-001 trial, radiotherapy was shown to improve progression-free survival and OS among NSCLC patients treated afterward with pembrolizumab 17. These findings warrant further trials to more fully assess the long-term impact of radiotherapy in combination with immunotherapy53.…”
Section: Discussionmentioning
confidence: 96%